The Effect of Applying Arabic Translation Techniques on the Translation Quality Assessment of Al Jazeera Captions on TikTok Social Media - Mas, Farrah Chaiya; Anis, Muhammad Yunus (Arabiyatuna: Jurnal Bahasa Arab, 2024)
The purpose of this study is to analyze the level of accuracy of Arabic caption translation on TikTok @aljazeera social media from the perspective of techniques and types of captions used to ensure whether the results of caption translation with the source language, namely Arabic on TikTok @aljazeera social media can be well received by readers in the target language, namely Indonesian. TikTok is one of the popular social media platforms today where the Qatari news account, @aljazeera, shares news in Arabic with captions to explain the uploaded videos. The data in this study are captions on TikTok @aljazeera social media which amounted to 66 data in Arabic and translated into Indonesian which amounted to 66 caption data. This research uses a qualitative descriptive linguistic design. Data collection was carried out by observation from July 1, 2023 to July 31, 2023. Data analysis used Spradley's model, such as: domain analysis, taxonomy analysis, componential analysis, and cultural theme analysis. The results of this study show that the types of captions in @aljazeera are: (1) identification, (2) story-telling, (3) summary, (4) quote, and (5) cutline. The findings and analysis of caption translation techniques in TikTok @aljazeera are: (1) conventional equivalence, (2) reduction, and (3) borrowing. The quality of translation in terms of accuracy is 32.27%, acceptability is 34.43%, and the readability aspect is 33.29%. The contribution of this research shows that the reduction technique has a significant impact on the decrease of translation quality assessment.